Pengaruh Disiplin Kerja, Gaya Kepemimpinan, dan Motivasi Kerja Intrinsik terhadap Kinerja Karyawan PT. Valbury Asia Futures Semarang - Nicolas Permadi; Ismi Darmastuti (Faculty of Economics and Business Diponegoro University, 2025)
This study examines the influence of work discipline, leadership style, and intrinsic work motivation on employee performance at PT. Valbury Asia Futures Semarang. Using a quantitative survey approach, data were collected through questionnaires from 38 employees. The results of multiple linear regression analysis show that all three variables jointly have a significant impact on employee performance. Partially, work discipline has the strongest effect, followed by intrinsic motivation, while leadership style shows no significant influence. The findings highlight the importance of strengthening discipline, enhancing intrinsic motivation, and adapting leadership approaches to improve performance outcomes.